(6x-5)/(x+5)=(x/3)-5
Answers
Answered by
3
6x-5=(x+5)(x-15)/3
=(6x-5)×3=(x+5)(x-15)
=18x-15=x^2-10x-75
=x^2-28x-60=0
= x^2-30x+2x-60=0
=x(x-30)+2(x-30)=0
=(x-30)(x+2)=0
=x=30
x=-2
=(6x-5)×3=(x+5)(x-15)
=18x-15=x^2-10x-75
=x^2-28x-60=0
= x^2-30x+2x-60=0
=x(x-30)+2(x-30)=0
=(x-30)(x+2)=0
=x=30
x=-2
stock:
Thnx a lot mam
Answered by
1
( 6x - 5 ) / ( x + 5 ) = ( x / 3 ) - 5
=> ( 6x - 5 ) / ( x + 5 ) = ( x - 15 ) / 3
=> 3( 6x - 5 ) = ( x - 15 ) ( x + 5 )
=> 18x - 15 = x^2 + 5x - 15x - 75
=> x^2 - 10x - 18x - 75 + 15 = 0
=> x^2 - 28x - 60 = 0
=> x^2 - ( 30 - 2 )x - 60 = 0
=> x^2 - 30x + 2x - 60 = 0
=> x( x - 30 ) + 2(x - 30 ) = 0
=> ( x - 30 ) ( x + 2 ) = 0
x + 2 = 0 Or x - 30 = 0
x = - 2 Or x = 30
Similar questions